2018
DOI: 10.1021/acs.jpca.8b00828
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Using High-Intensity THz Pulses To Induce Ultrafast Temperature-Jumps in Liquid Water

Abstract: Ultrashort, high-intensity terahertz (THz) pulses, e.g., generated at free-electron laser facilities, allow for direct investigation as well as the driving of intermolecular modes in liquids like water and thus will deepen our understanding of the hydrogen bonding network. In this work, the temperature-jump (T-jump) of water induced by THz radiation is simulated for ten different THz frequencies in the range from 3 to 30 THz and five different pulse intensities in the range from 1 × 10 to 5 × 10 W/cm employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 108 publications
0
26
0
Order By: Relevance
“…The analysis in this work is based on ab initio molecular dynamics (AIMD) trajectories of THz-pumped water that were the subject of previous work 21 sampled ten initial conditions with a time separation of 300 fs. Since the the PBE functional underestimates diffusion constants and prolongates equilibration times 39 , this resulted in a slightly favored orientation of the water molecules in the initial trajectory snapshots with cos ϑ = 0.08 .…”
Section: A Ab Initio Molecular Dynamics Trajectoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis in this work is based on ab initio molecular dynamics (AIMD) trajectories of THz-pumped water that were the subject of previous work 21 sampled ten initial conditions with a time separation of 300 fs. Since the the PBE functional underestimates diffusion constants and prolongates equilibration times 39 , this resulted in a slightly favored orientation of the water molecules in the initial trajectory snapshots with cos ϑ = 0.08 .…”
Section: A Ab Initio Molecular Dynamics Trajectoriesmentioning
confidence: 99%
“…We investigated the possibility of detecting ultrafast THz-induced T-jumps in liquid water by employing XUV photoelectron spectroscopy. The structural changes induced by sub-picosecond, high-intensity THz pulses of various frequencies were analyzed by calculating RDFs, building on AIMD trajectories that were the subject of previous work 21 . We found that, for a lower intensity, the loss of order is frequency-dependent.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations